Upaya Pencegahan Stunting Melalui Program Pemberian Makan Tambahan (PMT) di Desa Sukamulya - Pina Maelani Putri; Azfi Azfiyani; Elnaeni Badzlina; Hilma Nanda Musyafa; Putri Amanah; Sherina Lidya Hakim; Vonny Viviani; Aulia Putri Salsabila; Fikfik Taufik (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Stunting, a significant global health concern, is a condition where children suffer from impaired growth and development due to poor nutrition. This study evaluates the